2014
DOI: 10.1104/pp.113.233601
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Plant Drought Stress Response Using Terahertz Time-Domain Spectroscopy  

Abstract: We present a novel measurement setup for monitoring changes in leaf water status using nondestructive terahertz time-domain spectroscopy (THz-TDS). Previous studies on a variety of plants showed the principal applicability of THz-TDS. In such setups, decreasing leaf water content directly correlates with increasing THz transmission. Our new system allows for continuous, nondestructive monitoring of the water status of multiple individual plants each at the same constant leaf position. It overcomes previous dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 16 publications
1
70
0
Order By: Relevance
“…This includes gases [44][45], liquids [46], liquid crystals [47][48], and different types of solids [49][50][51][52][53]. But also artwork [54] and plants [55][56] have been investigated by THz-TDS.…”
Section: Introductionmentioning
confidence: 99%
“…This includes gases [44][45], liquids [46], liquid crystals [47][48], and different types of solids [49][50][51][52][53]. But also artwork [54] and plants [55][56] have been investigated by THz-TDS.…”
Section: Introductionmentioning
confidence: 99%
“…The Terahertz (THz) Imaging-System Analysis has been used in medical applications (Pickwell-MacPherson and Wallace, 2009;Smith and Arnold, 2011) and more recently, water content determination in leaves (Castro-Camus et al, 2013;Born et al, 2014;Gente and Koch, 2015). Water has a typical resonance that can be measured when it is applied at a frequency between 0.14 and 0.22 THz.…”
Section: Water Distribution In Leaves Evaluated Using Active Terahertmentioning
confidence: 99%
“…THz technology is a rapidly expanding field (Jepsen et al, 2011), and several agricultural applications have been identified, including measuring plant drought stress (Born et al, 2014) and leaf dehydration (Castro-Camus et al, 2013), estimating aflatoxin in peanut oil (Chen and Xie, 2014), and other applications summarized by Mathanker et al (2013). Various methods (Tonouchi, 2007) have been developed to generate and detect THz waves, but THz timedomain spectroscopy (THz-TDS) (Vieweg et al, 2014;Withayachumnankul and Naftaly, 2014) is considered the most powerful and widely used scheme.…”
mentioning
confidence: 99%
“…THz-TDS uses ultrashort laser pulses and photoconductive antennas (Hunsche et al, 1998;Moreno et al, 2014;Tani et al, 1997) or nonlinear crystals (Moreno et al, 2014). THz-TDS has been used to characterize solids (Jiang et al, 2014;LloydHughes et al, 2006;Misochko et al, 1998;Nickel et al, 2014;Wietzke et al, 2011), liquids (Wang et al, 2014), liquid crystals (Reuter et al, 2013;Vieweg et al, 2010), gases (Harde et al, 1995;Mittleman et al, 1998), and plants (Born et al, 2014;Castro-Camus et al, 2013).…”
mentioning
confidence: 99%